A Patient With Stage III Locally Advanced Pancreatic Adenocarcinoma Treated With Intra-Arterial Infusion FOLFIRINOX: Impressive Tumoral Response and Death due to Legionella pneumophila Infection: A Unique Case Report - Ranieri, Girolamo; Sablone, Sara; Fazio, Vito; De Ceglia, Dario; Porcelli, Mariangela; Molinari, Pasquale; Fucci, Livia; Laface, Carmelo; Gadaleta, Cosmo Damiano (Frontiers in Oncology, 2022)
Patients affected by pancreatic ductal adenocarcinoma (PDAC) have very poor prognosis,whereby at a follow-up of 5 years, the mortality rate is very similar to the incidence rate. Globally,around 10% of patients are amenable to radical surgery at the time of diagnosis,which represents the only chance of cure or long-term survival for these patients. Almost 40% of patients with PDACshow locally advanced pancreatic cancer (LAPC). LAPC is not a metastatic disease, although it is not amenable to radical surgery.For these patients, systemic induction chemotherapy with intravenous FOLFIRINOX (5-fluorouracil, folic acid, irinotecan, oxaliplatin) regimen is administered, with the aim of conversion to surgery,although the conversion rate remains low, at approximately 10% to 15%. Pancreatic arterial chemotherapy has been explored to overcome the intrisic tumor pancreatic resistance to systemic chemotherapy, where an intra-arterial port-a-cath is placed by means of interventional oncology techniquesunder angiographic guidancein the operatingtheater. Here, we treated a patient with an intra-arterial modified FOLFIRINOX regimen. Three courses were administered, and the patient experienced no adverse events. At the end of the third course, the patient rapidlydeveloped lung failure due to nosocomial Legionella pneumophila infection, despitethe impressive pathological tumor response showninthe autopsy report. This is a first and unique report that demonstratesthat pancreatic intra-arterial FOLFIRINOX can besafe and efficacious.We believe that this preliminary result will be confirmed in the next patients to be enrolled, and that itprovides a glimmer of hopefor patients with this lethal disease.